Microfibrillar-associated protein 4 interaction with inflammation and clinical characteristics in neuropsychiatric systemic lupus erythematosus - Wegener, Maria Alexandra Bandehkhoda; Möller, Sören; Olesen, Mads Nikolaj; Madsen, Jonna Skov; Sorensen, Grith Lykke; Voss, Anne; Asgari, Nasrin (Frontiers in Lupus, 2024)
Objectives Central nervous system (CNS) proteins such as neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) are released into the body fluids following CNS injury. Microfibrillar-associated protein 4 (MFAP4) is an extracellular matrix protein. Recently we reported expression of MFAP4 in CNS and alteration of levels in patients with acute neuroinflammation. We aimed to determine the levels of MFAP4 in a predominantly population-based cohort of systemic lupus erythematosus (SLE) patients, including neuropsychiatric SLE (NPSLE), and to evaluate MFAP4 as a marker of inflammation. Methods In total 208 SLE patients, 44 of those with NPSLE, and 50 age- and sex-matched healthy controls (HC) were recruited. MFAP4 was measured using AlphaLISA immunoassay. NfL, GFAP and a panel of inflammatory mediators were measured using Simoa HD-1 digital ELISA or a Luminex 200 instrument. Results MFAP4 levels were elevated in patients with NPSLE compared to patients with non-NPSLE (p = 0.031), more prominent in NPSLE patients with CNS involvement (p = 0.017). NfL and GFAP were higher in the total SLE cohort (p < 0.001, p < 0.001, respectively) as well as NPSLE subgroup (p < 0.001, p < 0.001, respectively), and in the subgroup of NPSLE patients with CNS involvement (p < 0.001, p < 0.001), compared to HC. NfL and GFAP levels correlated positively with MFAP4 in the NPSLE as well as the non-NPSLE subgroup (ρ = 0.44, p = 0.003, ρ = 0.25, p = 0.004). VEGF was reduced in NPSLE patients compared to HC (p = 0.015). MMP-9 was elevated in NPSLE compared to non-NPSLE (p = 0.048). Inflammatory markers including IFN-α, IL-6, IL-10 and TNF-α, were elevated in the NPSLE group compared to HC (p < 0.001, p = 0.0026, p = 0.042, p = 0.007, respectively). In NPSLE patients the levels of MFAP4 correlated with TNF-α (p = 0.016) and IL-17 (p = 0.0044) and with markers of blood brain barrier (BBB) disruption MMP-7 (p = 0.005) and VEGF (p < 0.001). In NPSLE patients with CNS manifestations MMP-3 and VEGF correlated with MFAP4 (p = 0.011, p = 0.0004, respectively). Conclusion Levels of MFAP4 correlated with NfL, GFAP and proinflammatory cytokines and in NPSLE additionally with markers of BBB disruption, suggesting that MFAP4 is a marker of inflammation and vascular re-organization. Correlation of NfL and GFAP with MFAP4 may reflect CNS tissue damage.